Interleukin-27 Enforces Regulatory T Cell Functions to Prevent Graft-versus-Host Disease - Le, Hongnga T.; Keslar, Karen; Nguyen, Quang Tam; Blazar, Bruce R.; Hamilton, Betty K.; Min, Booki (Frontiers in Immunology, 2020)
Graft-versus-host disease (GvHD) remains a significant complication of allogeneic hematopoietic cell transplantation (HCT), associated with significant morbidity and mortality. GVHD is characterized by a dysregulated immune response with resulting tissue damage of target organs. Recent investigations have focused on Foxp3+ regulatory T cells (Tregs) as a therapeutic tool, based on its regulatory functions in GvHD pathogenesis and their instrumental role in mitigating GvHD severity while preserving graft-versus leukemia (GvL) activity. There are several challenges to its clinical application, including their paucity, impaired suppressive activity, and instability in vivo. Herein, we report that IL-27 pre-stimulation enhances suppressive functions to both mouse and human Tregs. In a complete MHC mismatched murine bone marrow transplant model, IL-27 pre-stimulated polyclonal iTregs diminish acute (a)GvHD lethality, while preserving the GvL effect. Allo-antigen specificity further improves suppressive functions when combined with IL-27 pre-stimulation. In a xenogeneic (human to mouse) GvHD model, IL-27 pre-stimulated human iTregs are superior in protecting recipients from GvHD. Lastly, we compared gene expression profiles of circulating Tregs isolated from HCT recipients with and without aGvHD and found that Tregs from aGvHD patients express distinct gene signatures enriched in immune activation and inflammation. Therefore, these results highlight a novel function of IL-27 in enforcing Treg functions to prevent aGvHD mediated lethality, proposing the hypothesis that dysregulated Treg functions may account for the potential mechanisms underlying GvHD development.